Suppression of UVB-Induced MMP-1 Expression in Human Skin Fibroblasts Using Lysate of Lactobacillus iners Derived from Korean Women’s Skin in Their Twenties - Lee, Jin Sung; Min, Jin Woo; Gye, Seong Bong; Kim, Yong Woo; Kang, Hee Cheol; Choi, Yoon Seo; Seo, Won Sang; Lee, Bun Yeoul (Current Issues in Molecular Biology, 2024)
The process of skin aging is intricate, involving intrinsic aging, influenced by internal factors, and extrinsic aging, mainly caused by exposure to UV radiation, resulting in photoaging. Photoaging manifests as skin issues such as wrinkles and discoloration. The skin microbiome, a diverse community of microorganisms on the skin’s surface, plays a crucial role in skin protection and can be affected by factors like humidity and pH. Probiotics, beneficial microorganisms, have been investigated for their potential to enhance skin health by regulating the skin microbiome. This can be accomplished through oral probiotics, impacting the gut–skin axis, or topical applications introducing live bacteria to the skin. Probiotics mitigate oxidative stress, suppress inflammation, and maintain the skin’s extracellular matrix, ultimately averting skin aging. However, research on probiotics derived from human skin is limited, and there is no established product for preventing photoaging. The mechanism by which probiotics shield the skin microbiome and skin layers from UV radiation remains unclear. Recently, researchers have discovered Lactobacillus in the skin, with reports indicating a decrease in this microorganism with age. In a recent study, scientists isolated Lactobacillus iners KOLBM20 from the skin of individuals in their twenties and confirmed its effectiveness. A comparative analysis of genetic sequences revealed that strain KOLBM20 belongs to the Lactobacillus genus and closely relates to L. iners DSM13335(T) with a 99.20% similarity. Importantly, Lactobacillus iners KOLBM20 displayed anti-wrinkle properties by inhibiting MMP-1. This investigation demonstrated the inhibitory effect of KOLBM20 strain lysate on MMP-1 expression. Moreover, the data suggest that KOLBM20 strain lysate may prevent UVB-induced MMP-1 expression by inhibiting the activation of the ERK, JNK, and p38 signaling pathways induced by UVB. Consequently, KOLBM20 strain lysate holds promise as a potential therapeutic agent for preventing and treating skin photoaging.
Keywords: 16S rRNA; ERK; human skin derived probiotics; JNK; Lactobacillus; MMP-1; p38; UVB-induced